2015
DOI: 10.1097/bpo.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Treatment of Displaced Proximal Humeral Physeal Fractures

Abstract: Level III-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 10 publications
2
52
0
1
Order By: Relevance
“…Among several studies that have examined functional outcomes after percutaneous pinning of pediatric proximal humeral fractures 3 . There were no differences in functional outcomes, complications, or rate of return to preinjury activity; however, less than desirable outcomes were noted in patients at least 12 years old who were managed nonoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…Among several studies that have examined functional outcomes after percutaneous pinning of pediatric proximal humeral fractures 3 . There were no differences in functional outcomes, complications, or rate of return to preinjury activity; however, less than desirable outcomes were noted in patients at least 12 years old who were managed nonoperatively.…”
Section: Resultsmentioning
confidence: 99%
“…19 studies were analysed for the above-named parameters. [ 6 9 , 12 17 , 26 – 29 ] Quality assessment led to a calculation of a mean Coleman Methodology Score of 70.95 ± 7.41 points (range 57–86 points, confer Table 1 ). One study was of Level III evidence according to the Oxford Centre for Evidence-based Medicine, 18 studies were of Level IV evidence.…”
Section: Resultsmentioning
confidence: 99%
“…All of the conservatively treated patients with a less than desirable outcome were at least 13 years of age. [ 26 ] Dameron et al reported patients who had limitations in their final range-of-motion; all of them were 14 years and older. [ 5 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations